TEACHING AND LEARNING BY COMPLEX THOUGHT: A CINEMATOGRAPHIC ILUSTRATION - Vieira Leite, Monica Regina [UNESP]; Leite, Jose Ribeiro; Ferreira, Patricia Osorio [UNESP] (Univ Federal Mato Grosso Sul, 2018)
Teaching and learning, more than verbs that indicate an action, more than activities, are an action involved in a series of questions, whether they are methodological, philosophical, social, political, etc. Hence the difficulties and challenges faced by teachers and students and the need to find or create means of execution of this action that can lead to the achievement of the expected results. With this unease, we chose to study audiovisual resources, particularly films, and its importance for teaching by complex thought, which stands out for being dynamic, creative, unpredictable, non-linear and able to connect subjects. It is a theory that serves as a network of information created by these connections, defragmenting the thought and offering a broader and enlightening view of the world. This research is of bibliographical nature, accompanied by an analysis of illustrative films, chosen based on their potential for teaching through complex thought and for addressing socio-environmental themes. In addition to the introduction and the final considerations, the use of audiovisual resources, complex thought and cinematic illustration in teaching were analyzed. We concluded that the films, when working with the objective of developing complex thought, allow us to understand that all the areas of study addressed by them are related within the reality in which we live and, when interconnected, form the whole. In addition, it is a resource that attracts and motivates students, facilitating learning and contributing to making it more enjoyable and comprehensive.
Keywords: Teaching; Learning; Movie; Defragmentation